Distinct Actions and Cooperative Roles of ROCK and mDia in Rho Small G Protein-induced Reorganization of the Actin Cytoskeleton in Madin–Darby Canine Kidney Cells - Nakano, Katsutoshi (The American Society for Cell Biology, 1999)
Rho, a member of the Rho small G protein family, regulates the formation of stress fibers and focal adhesions in various types of cultured cells. We investigated here the actions of ROCK and mDia, both of which have been identified to be putative downstream target molecules of Rho, in Madin–Darby canine kidney cells. The dominant active mutant of RhoA induced the formation of parallel stress fibers and focal adhesions, whereas the dominant active mutant of ROCK induced the formation of stellate stress fibers and focal adhesions, and the dominant active mutant of mDia induced the weak formation of parallel stress fibers without affecting the formation of focal adhesions. In the presence of C3 ADP-ribosyltransferase for Rho, the dominant active mutant of ROCK induced the formation of stellate stress fibers and focal adhesions, whereas the dominant active mutant of mDia induced only the diffuse localization of actin filaments. These results indicate that ROCK and mDia show distinct actions in reorganization of the actin cytoskeleton. The dominant negative mutant of either ROCK or mDia inhibited the formation of stress fibers and focal adhesions, indicating that both ROCK and mDia are necessary for the formation of stress fibers and focal adhesions. Moreover, inactivation and reactivation of both ROCK and mDia were necessary for the 12-O-tetradecanoylphorbol-13-acetate–induced disassembly and reassembly, respectively, of stress fibers and focal adhesions. The morphologies of stress fibers and focal adhesions in the cells expressing both the dominant active mutants of ROCK and mDia were not identical to those induced by the dominant active mutant of Rho. These results indicate that at least ROCK and mDia cooperatively act as downstream target molecules of Rho in the Rho-induced reorganization of the actin cytoskeleton.